Shabu ; Spolarium ; Martin [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1988)
Probe examines the "poor man's cocaine" ; restoration of Juan Luna's masterpiece which causes a controversy over the methods and the credentials of the restorer ; and interview with Martin Nievera about his singing carrer and his family.
Shabu (15 min.) -- Spolarium (15 min) -- Martin (12 min.)
VHS.
Keywords: Nievera, Martin. Interviews; Shabu; Narcotic addicts -- Rehabilitation; Narcotic habit -- Treatment; Art -- Conservation and restoration; Paintings -- PhilippinesxConversation and restoration